Thermal hydraulic safety characteristics analysis for the natural circulation primary loop under inclined condition on LFR - Jinting Liu; Jinting Liu; Tingyu Li; Tingyu Li; Tingyu Li; Yang Li; Yang Li; Yang Li; Danna Zhou; Danna Zhou; Danna Zhou; Dajian Yu; et al. (Frontiers in Energy Research)
Lead-cooled fast reactor (LFR) has been an important option for floating nuclear power plant. The design of 50 MW natural circulation LFR had been proposed by Lanzhou University for floating nuclear power plant. However, floating nuclear power plant was affected by the marine environment, which led to safety problems in reactor under inclined condition. To analyze the impact of different heat exchangers configuration and inclination angle on the thermal-hydraulic safety performance of the reactor, this study utilized RELAP5 software and established a thermal-hydraulic model of the 50 MW natural circulation LFR. The results indicated that the core flow rate reduced to 95.12% of the flow rate at 100%FP power, when the inclination angle was 30°. When the angle between the heat exchanger and the central axis of floating nuclear power plant is 45°, the maximum outlet temperature difference in the heat exchanger is 1.86K. During the process of power increasing and decreasing, the reactor power was increased with rates of 0.5% FP/min, and the core cladding temperature was increased to the maximum 938.42K. This study provided technical reference for the design of natural circulation lead-cooled fast reactors in floating nuclear power plant.